A C‐shaped dielectric resonator antenna with frequency reconfigurable for ISM and LTE band applications. Issue 1 (January 2017) - Danesh, S.; Kamarudin, M. R.; Rahman, T. A.; Abedian, M.; Jamaluddin, M. H.; Khalily, M.
ABSTRACT: A frequency tunable dielectric resonator antenna (DRA) is studied and presented for ISM and LTE band applications. Here, the frequency operation of the proposed DRA is switched from dual band to narrowband mode by using the PIN diode switches. The switches are employed by RF PIN diodes and placed on the feed line network to excite the dielectric resonator (DR). The proposed reconfigurable DRA has a compact size with a thickness of 3 mm and the overall size of 30 × 37 mm 2 that is proper for mobile devices. The measured and simulated results indicate that the proposed DRA provides a single and dual band modes which covers the ISM applications and 2.6 GHz LTE system, respectively. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:134–138, 2017